2017
DOI: 10.13102/sociobiology.v64i3.1257
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Pollen Stored by Melipona mandacaia (Smith, 1863) (Hymenoptera: Apidae, Meliponini) in an Urban Arid Landscape

Abstract: The objective of this study was to identify the species of pollen supplying plants that constitute the trophic niche of Melipona mandacaia in an urban area in the Caatinga domain (a tropical arid landscape). The collection of pollen in the colonies was carried out every 15 days, from October 2014 to September 2015. The pollen was removed directly from the storage pots in three distinct colonies. A total of 24 samples were analyzed and compared with the reference pollen collection, pollen catalogs and specializ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
3
0
4
Order By: Relevance
“…The pollen analyses of beehive products from the semi-arid region of Bahia show a major predominance for pollen stored by the bees (bee pollen) (Novais et al 2009;Oliveira et al 2016;Carneiro Neto et al 2017). However, honey is the best known and most consumed product of bees (Tsutsumi & Oishi 2010).…”
mentioning
confidence: 99%
“…The pollen analyses of beehive products from the semi-arid region of Bahia show a major predominance for pollen stored by the bees (bee pollen) (Novais et al 2009;Oliveira et al 2016;Carneiro Neto et al 2017). However, honey is the best known and most consumed product of bees (Tsutsumi & Oishi 2010).…”
mentioning
confidence: 99%
“…Las abejas sin aguijón son afectadas por el cambio de uso de suelo y la intensificación agrícola, siendo estas las principales causas de la disminución de estos polinizadores (Thomann et al, 2013;Carneiro-Neto et al, 2017). Por otra parte, las abejas son susceptibles a los agroquímicos como neonicotinoides, permetrina, diazinón, metomilo y organoclorados, los cuales tienen efectos letales y subletales sobre estas abejas, los cuales pueden ser ingeridos a través del néctar, el polen, el agua o cuando recolectan resinas y arcillas.…”
Section: Las Abejas Sin Aguijón Y La Polinizaciónunclassified
“…Para conservar la diversidad de abejas sin aguijón que contribuyen a la polinización de cultivos, es necesario mantener parches florales cercanos a las plantaciones que sirvan de alimento cuando el cultivo no está en floración (Carneiro-Neto et al, 2017). Asimismo, es importante garantizar la disponibilidad de recursos florales durante las estaciones del año, esto mediante la siembra de diferentes cultivos cuya floración, en conjunto, abarque todo el año (Vollet-Neto et al, 2018).…”
Section: Paísunclassified
“…The Fabaceae species, specifically Mimosa genus, have morphological features such as dense inflorescences with small and gently scented flowers that attract many species of stingless bees to collect trophic resources, such as pollen and nectar, highlighting the importance of this botanic family (Carneiro-Neto et al, 2017;Maia-Silva et al, 2012). In bee pollen samples evaluated by Almeida-Muradian et al (2005) and Estevinho et al (2012) pollen types of Fabaceae were also identified.…”
Section: Pollen Analysesmentioning
confidence: 99%